2015
DOI: 10.1111/bdi.12315
|View full text |Cite
|
Sign up to set email alerts
|

Interhemispheric resting state functional connectivity abnormalities in unipolar depression and bipolar depression

Abstract: Depressive episodes in BD and UD have similar impairments of interhemispheric coordination, which might imply an overlap in the neuropathology of depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(58 citation statements)
references
References 54 publications
2
54
2
Order By: Relevance
“…Most of the network differences in our study between these groups comprised inter-hemispheric differences. So far, there are several studies that show decreased inter-hemispheric FC in MDD 3640 . However, the biological background of inter-hemispheric FC abnormalities is not fully understood, although studies from split brain patients suggest that a disruption of inter-hemispheric FC affects the information processing and functioning of the brain 41, 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Most of the network differences in our study between these groups comprised inter-hemispheric differences. So far, there are several studies that show decreased inter-hemispheric FC in MDD 3640 . However, the biological background of inter-hemispheric FC abnormalities is not fully understood, although studies from split brain patients suggest that a disruption of inter-hemispheric FC affects the information processing and functioning of the brain 41, 42 .…”
Section: Discussionmentioning
confidence: 99%
“…The precuneus and PCC, the major hub nodes of the DMN, are related to a wide range of cognitive functions, such as episodic memory retrieval, modulation of emotionally salient memories, self-consciousness, and visuo-spatial imagery 37 . Several R-fMRI studies also indicated involvement of the precuneus/PCC in mood disorders, including abnormal spontaneous activity 38 and functional connectivity 28, 39–42 . Previous task-fMRI studies also reported abnormal activity in the precuneus/PCC in BD and MDD patients during cognitive and emotional tasks 43–45 .…”
Section: Discussionmentioning
confidence: 99%
“…The clinical state of each patient was assessed using the 24-item Hamilton Depression Rating Scale (HAMD) and the Young Mania Rating Scale (YMRS) during the seven-day period prior to the R-fMRI scan. The inclusive criteria were a HAMD-24 total score > 21 for the MDD patients and a YMRS total score < 7 and a HAMD-24 total score > 21 for the BD patients 28 . The exclusion criteria were patients with other Axis-I psychiatric disorders (except for UD, BD, and anxiety disorders), a history of organic brain disorder, neurological disorders, mental retardation, cardiovascular diseases, alcohol or substance abuse, pregnancy, or any physical illness.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, several studies have explored the differences in FC between BD and MDD using resting-state (Ellard et al 2015; Goya-Maldonado et al 2016; Marchand et al 2013; Wang et al 2015) or task-related fMRI (Anand et al 2009; Redlich et al 2015; Satterthwaite et al 2015). We previously studies compared neuroimaging data between BD and MDD by constructing the functional network connectivity (FNC), composed of a whole brain graph with nodes defined by independent components analysis (ICA) (Jafri et al 2008).…”
Section: Introductionmentioning
confidence: 99%